Preoperative prognostic nutritional index as a predictive factor for medical complication after cervical posterior decompression surgery: A multicenter study. (8th April 2021) - Kurosu, Kenta; Oe, Shin; Hasegawa, Tomohiko; Shimizu, Satoshi; Yoshida, Go; Kobayashi, Sho; Fujita, Tomotada; Yamada, Tomohiro; Ide, Koichiro; Watanabe, Yuh; Nakai, Keiichi; Yamato, Yu; et al.
Study design: Retrospective longitudinal cohort study. Objective: To investigate postoperative medical complications in patients with malnutrition after cervical posterior surgery. Methods: A total of 256 patients were participated and divided into PNI < 50 group (group L) or PNI ≥ 50 (group H). Patient data, preoperative laboratory data, surgical data, hospitalization data, JOA score, complication data were measured. Results: Group L and group H were 127 and 129 patients, each PNI was L: 44.8 ± 4.3, H: 54.6 ± 4.0, P < 0.01. There was significant difference in mean age (L: 72.2 years vs H: 64.8 years, P < 0.01), BMI (23.1 vs 24.7, P < 0.01), serum albumin (L: 3.9 ± 0.4 g/dl vs H: 4.4 ± 0.3 g/dl, P < 0.01), total lymphocyte count (L: 1.3 ± 0.5 10 3 /µL vs H: 2.1 ± 0.7 10 3 /μL, P < 0.01), hospital stay (L: 25.0 days vs H: 18.8 days, P < 0.05), discharge to home (87.5% vs 57.5%, P < 0.01), delirium (L: 15.9% vs H: 3.9%, P < 0.01), medical complications (L: 25.2% vs H: 7.0%, P < 0.01), pre- and post- operative JOA score (L: 11.3 ± 2.8 vs H: 12.4 ± 2.6, P < 0.01; L: 13.3 ± 3.0 vs H: 14.1 ± 2.4, P = 0.02). Multiple logistic regression analysis showed that significant risk factors for medical complications were PNI<50 (P = 0.024, odds ratio [OR] 2.746, 95% confidence interval [CI] 1.143–6.600) and age (P = 0.005, odds ratio [OR] 1.064, 95% confidence interval [CI] 1.020–1.111). Conclusion: Medical complications are significantly higher in patients with PNI < 50 and higher age. The results showed that PNI is a good indicator for perioperative medical complications in cervical posterior surgery. Improvement of preoperative nutritional status is important to avoid medical complications. Level of evidence: 3